A Case Report of Probable Paliperidone ER-Induced Serotonin Syndrome in a 17-Year-Old Taiwanese Female With New Onset Psychosis. Issue 9 (March 2016) - Yang, Chung-Hao; Juang, Kai-Dih; Chou, Po-Han; Chan, Chin-Hong
Abstract : Abstract: A 17-year-old female with new-onset psychosis was treated with paliperidone. After increasing the paliperidone dose to 12 mg per day the patient developed a series of side effects; Tachycardia (140 bpm), severe drooling, restlessness, diaphoresis, whole-body tremor, inducible foot clonus, predominant lower limbs rigidity, bilateral pupil dilation, increased bowel sounds with watery diarrhea, and muscle hypertonicity. The symptoms subsided after stopping the paliperidone, and recurred after resuming paliperidone 9 mg per day. To our knowledge, this is the first case of a very clear and close relationship between the symptoms of serotonin syndrome and the use of paliperidone. We have to cautiously consider the diagnosis of serotonin syndrome in potential cases.